PROBE Study: A Sentinel Surveillance System to Monitor Exposure of Belgian Employees to Hazardous Chemicals. Issue 12 (December 2020) - Pauwels, Sara; Swinnen, Celien; Temmerman, Anne-Marie; Ronsmans, Steven; Rusu, Dorina; De Schryver, Antoon; Braeckman, Lutgart; Godderis, Lode
Abstract : Objective: To test the feasibility of collecting reliable and representative data on exposure of Belgian employees to a selection of hazardous chemicals by using a sentinel surveillance method. Method: In PROBE (Hazardous chemical P roducts R egister for O ccupational use in Be lgium), 47 occupational physicians were recruited as a sentinel network. Employees answered a web-based survey assessing their past week exposure to 22 chemicals. Results: 47% employees were exposed to at least one chemical. The most frequently reported exposures was to diesel exhaust (14%). The exposed employees were mostly older men, with most exposed during production and manufacturing, and working in smaller companies. For diesel exhaust, wood dust, and crystalline silica, 54%, 32%, and 20% of the exposed employees, did not use collective/personal protective equipment. Conclusion: Sentinel surveillance is a feasible method for obtaining high-quality data on the exposure of Belgian employees to hazardous chemicals. Abstract : Supplemental Digital Content is available in the text